Short- and long-term performance of bonding steel-plate joints for timber structures. (20th April 2020) - Shi, Benkai; Yang, Huifeng; Liu, Jianzheng; Crocetti, Roberto; Liu, Weiqing
Highlights: Ultimate bearing capacity of bonding steel-plate joints for timber structures. Creep trends and coefficients of bonding steel-plate joints with different stress levels. Creep coefficients predictions of joints in the duration of service life. Long-term slip stiffness and the ratio of stiffness reduction for bonding steel-plate joints. Abstract: The long-term performance of bonding steel-plate joints in controlled environmental conditions in this work. The bonding steel-plate joint consists of a steel plate with a vulcanized rubber layer and six wood screws. The vulcanized rubber layer is intended to improve the ductility of bonding steel-plate joints. Six pull-pull specimens were tested in order to determine the short-term load bearing capacity of bonding steel-plate joints, and the dimension of the shear plane of each bond line was 80 mm × 80 mm. A total of 12 specimens were employed in long-term tests. Two stress levels, including the 30% and 60% of ultimate bearing capacity, were adopted. All specimens were monitored over 800 days except that one series of specimens with 0.6 stress level which failed during the long-term tests. At the end of 858-day loading, the average slip at the connection for the specimens with 30% and 60% stress level were 0.623 mm and 0.939 mm, respectively. The creep coefficients were calculated according to the measured experimental data. The Burger's model, two term and six term Kelvin's model were adopted to fit the curves of creep coefficients, and then predict the creep slip of joints in the duration of service. The long-term slip stiffness and the ratio of stiffness loss are calculated according to experimental curves, and are predicted on the basis of the prediction results of creep coefficients through by six term Kelvin's model.